Acrocallosal Syndrome (Schinzel Syndrome) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The acrocallosal syndrome, first described by Schinzel and characterized by dysmorphic features, macrocephaly, Polydactyly, mental retardation, and agenesis of the corpus callosum, is reported in two unrelated boys with consanguineous parents from the Centre de Génétique Médicale, Service de Pediatrie Générale and Radiologie, Hôpital d'Enfants de la Timone, Marseille, France.